Properties of Arctic aerosol in the transition between Arctic haze to summer season derived by lidar - Eggers, Nele (Dr.) (2023)
During the Arctic haze period, the Arctic troposphere consists of larger, yet fewer, aerosol particles than during the summer (Tunved et al., 2013; Quinn et al., 2007). Interannual variability (Graßl and Ritter, 2019; Rinke et al., 2004), as well as unknown origins (Stock et al., 2014) and properties of aerosol complicate modeling these annual aerosol cycles. This thesis investigates the modification of the microphysical properties of Arctic aerosols in the transition from Arctic haze to the summer season. Therefore, lidar measurements of Ny-Ålesund from April 2021 to the end of July 2021 are evaluated based on the aerosols’ optical properties. An overview of those properties will be provided. Furthermore, parallel radiosonde data is considered for indication of hygroscopic growth. The annual aerosol cycle in 2021 differs from expectations based on previous studies from Tunved et al. (2013) and Quinn et al. (2007). Developments of backscatter, extinction, aerosol depolarisation, lidar ratio and color ratio show a return of the Arctic haze in May. The haze had already reduced in April, but regrew afterwards. The average Arctic aerosol displays hygroscopic behaviour, meaning growth due to water uptake. To determine such a behaviour is generally laborious because various meteorological circumstances need to be considered. Two case studies provide further information on these possible events. In particular, a day with a rare ice cloud and with highly variable water cloud layers is observed. Während der Arctic haze Periode sind größere, jedoch auch weniger, Aerosole in der arktischen Troposphäre vorhanden als im Sommer (Tunved et al., 2013; Quinn et al., 2007). Interannuale Variabilität (Graßl and Ritter, 2019; Rinke et al., 2004), sowie unbekannte Herkunft (Stock et al., 2014) und Eigenschaften der Aerosole erschweren die Modellierung der Aerosol-Jahresgänge. Diese Arbeit untersucht, wie sich die mikrophysikalischen Eigenschaften der Aerosole beim Übergang vom Arctic haze zur Sommerzeit ändern. Dafür werden Lidar ...